2020
DOI: 10.1021/acs.jpclett.9b03752
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Orientation and Vibronic Couplings between Electronic and Vibrational Coordinates with Polarization-Selective Two-Dimensional Vibrational-Electronic Spectroscopy

Abstract: We experimentally demonstrate polarization-selective two-dimensional (2D) vibrational-electronic (VE) spectroscopy on a transition-metal mixed-valence complex where the cyanide stretching vibrations are coupled to the metal-to-metal charge-transfer transition. A simultaneous fitting of the parallel and crossed polarized 2D VE spectra quantifies the relative vibronic coupling strengths and angles between the charge-transfer transition and three coupled cyanide stretching vibrations in a mode-specific manner. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Recent development of broad band spectrometers [269][270][271] and spectroscopies combining very different spectral regions 160,272,273 provides new opportunities to probe interactions between states with very different energies and to simultaneously probe dynamics over broad spectral ranges. At the same time, this poses new challenges to the computational approaches to include the relevant states at an equal level of theory.…”
Section: Concluding Discussion and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent development of broad band spectrometers [269][270][271] and spectroscopies combining very different spectral regions 160,272,273 provides new opportunities to probe interactions between states with very different energies and to simultaneously probe dynamics over broad spectral ranges. At the same time, this poses new challenges to the computational approaches to include the relevant states at an equal level of theory.…”
Section: Concluding Discussion and Future Directionsmentioning
confidence: 99%
“…150 A wide range of other non-linear spectroscopic techniques is available providing insight into different sample properties. 7,14,[151][152][153][154][155][156][157][158][159][160][161] A significant effort has been invested in the efficient calculation of two-dimensional spectroscopic signals. 46,89,162,163…”
Section: G Spectral Simulationsmentioning
confidence: 99%
“…Time-resolved optical spectroscopy, infrared (IR) and 2D spectroscopies have made important measurements of ultrafast charge transfer in mixed valence systems by measuring relevant solvent-dependent kinetic parameters of electron transfer and identifying the role of the coupled high-frequency cyanide vibrations in the photoinduced forward and back electron transfer processes. [3][4][5][6][7][8][9][10] These ultrafast studies have shown that two properties play key roles in electron transport: vibronic coupling and electron delocalization. 5,[11][12][13][14] Both properties control the dispersal of energy during electron transfer and ultimately determine the geometric and electronic changes during excitation and relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…Its properties have been been studied extensively optically and in particular 2D vibrational-electronic spectroscopy shows that the cyanide bridge stretching mode is strongly coupled to the MMCT transition and becomes excited following the electronic excitation. 4,9,[37][38][39] Transient optical experiments have reported an ultrafast back electron transfer (BET) time of 89 ± 10 fs, 3 implying that ultrafast and spatially localized measurements are necessary for characterizing the BET. Additionally, a recent ultrafast X-ray scattering experiment demonstrated how coherent solvent motions play an important role in the BET dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Twodimensional (2D) vibrational spectroscopy (2DVS) [31][32][33] and 2D electronic spectroscopy (2DES) have been applied to condense phase transition and succeeded in investigating the electronic excitation dynamics and a structural change of molecules. [34][35][36][37][38] Their combination, 2D electronicvibrational spectroscopy (2DEVS), has also been successfully applied to the photo-isomerization reactions, mental-to-ligands transitions, conical intersection wavepacket dynamics, and ultrafast excitonic photosynthetic energy transfer reactions. [39][40][41][42][43] By utilizing the UV-vis and IR pulses, we are now able to measure the coupling strength and coherence between the electronic and vibrational transitions as the off-diagonal peaks of 2D spectroscopy.…”
Section: Introductionmentioning
confidence: 99%